Friendly Faces: Characteristics of Children and Adolescents With Repeat Visits to a Specialized Child Psychiatric Emergency Program. Issue 1 (January 2021) - Marr, Mollie; Horwitz, Sarah M.; Gerson, Ruth; Storfer-Isser, Amy; Havens, Jennifer F.
Abstract : Objectives: Pediatric mental health emergency department (ED) visits continue to rise with 19% to 62% of youth presenting to the ED ultimately returning for a mental health–related complaint. To better understand the needs of children returning to the ED, this study examines the clinical, demographic, and environmental factors associated with revisits to a dedicated child psychiatric ED. Methods: Clinical factors, home environment, and mental health service utilization of 885 children presenting to a dedicated child psychiatric ED over a 1-year period were abstracted by retrospective chart review. Bivariate analyses comparing demographic and clinical characteristics for children with and without revisits and a multivariable logistic regression were performed. Results: Of the children presenting to the ED, 186 (21.0%) had at least 1 revisit in the subsequent 180 days. Thirty-one percent of initial visits presented as urgent, 55% presented as emergent. Children presenting with more severe symptoms at their initial visit were more likely to return within 6 months. Female gender, suicidal and disruptive behavioral symptomatology, and a diagnosis of oppositional defiant disorder were associated with repeat visits. Children with mental health system involvement were more likely to have revisits than those who were "treatment naive." Conclusions: Revisits to the ED are driven by both clinical factors, including severity and psychosocial complexity, and barriers to accessing services. Addressing the problem of return ED visits will require the development of a robust mental health service system that is accessible to children and families of all socioeconomic levels.